Effective academic writing 1: - Savage, Alice (Oxford University Press, 2007)
Effective Academic Writing, Second Edition provides the tools necessary for successful academic writing: Step-by step Writing Process guides and refines writing skills. Timed Writing practice prepares students for success on high-stakes tests. Online Writing Tutor on Oxford Learn improves academic writing inside and outside the classroom. Online Grammar Practice provides extra practice where and when your students need it the most.